2005
DOI: 10.1002/ajmg.a.30927
|View full text |Cite
|
Sign up to set email alerts
|

Cleidocranial dysplasia: Molecular genetic analysis and phenotypic‐based description of a Middle European patient group

Abstract: Cleidocranial dysplasia (CCD) (OMIM 119600) is a rare dysplasia of osseous and dental tissue. Characteristic features are typical facial and dental appearance plus morphologic anomalies. RUNX2 (OMIM 600211), the responsible gene for CCD, is considered to be a master gene for bone development and bone homeostasis. This study describes the genotype-phenotype correlation based on craniofacial features involving an interdisciplinary approach. Our patient cohort consisted of 31 CCD patients from 20 families; five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 24 publications
3
58
0
2
Order By: Relevance
“…We have attempted to tabulate the phenotypic features of the 5 patients (including our patient) presenting with normal clavicles. Baumert et al [2005] proposed a classification system for CCD which we found useful for eliciting the features and assigning a score. We scored the patients for each variable to reach the cumulative score for genotype-phenotype correlation ( table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have attempted to tabulate the phenotypic features of the 5 patients (including our patient) presenting with normal clavicles. Baumert et al [2005] proposed a classification system for CCD which we found useful for eliciting the features and assigning a score. We scored the patients for each variable to reach the cumulative score for genotype-phenotype correlation ( table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…c Patient 5 refers to the present study. Classification scheme given by Baumert et al [2005] was used in patients 1 -4. In all cases, shoulder mobility was zero (clavicles could not be approximated to midline).…”
Section: Discussionmentioning
confidence: 99%
“…It is a transcription factor involved in osteoblast differentiation from mesenchymal cells 5. Mutations in this gene are found in 60–70% of the participants clinically diagnosed with the condition and include missense, non-sense, deletions/insertions and splice site variations leading to premature termination 2 6 7…”
Section: Discussionmentioning
confidence: 99%
“…Numerous mutations in RUNX2 have been identified in patients with CCD (Otto et al 2002;Yoshida et al 2002;Zhou et al 1999). Most of the missense mutations were located in the runt region (Baumert et al 2005;Otto et al 2002;Yoshida et al 2002) involving heterodimerization and DNA binding with CBFb. This discrepancy in distribution could be explained by that the runt domain is highly conserved and is less resistant to single nucleotide changes.…”
Section: Introductionmentioning
confidence: 99%